Outcomes of anterior interosseous nerve transfer to restore intrinsic muscle function after high ulnar nerve injury. Issue 2 (February 2022) - George, Samuel C; Burahee, Abdus S; Sanders, Andrew D; Power, Dominic M
Summary: Traumatic high ulnar nerve injuries have historically resulted in long-term loss of hand function due to the long re-innervation distance to the intrinsic muscles. Transfer of the anterior interosseous nerve (AIN) to the deep motor branch of the ulnar nerve (MUN) is proving promising in these patients. The purpose of this study was to evaluate the outcomes and efficacy of this procedure in our series. Eligible high ulnar nerve injury patients who underwent AIN to MUN nerve transfer were evaluated with a mean follow-up of 17 months. Data including demographics, injury details, surgical procedures, and outcomes were collected. A review of the current literature was performed for comparison. Sixteen patients had AIN to MUN transfer, mean age of 39.4 years, and a median delay from injury to nerve transfer of 0.8 months. The injury site was above the elbow in 5 cases, at the elbow in 8 cases, and in the proximal forearm in 3 cases. The majority were sharp transection, with the remaining from blast injuries, traumatic traction, and one post-traumatic neuroma resection. Transfer was performed end-to-end in 7 cases, hemi end-to-end in 7 cases, and supercharged end-to-side in 2 cases. Five patients achieved intrinsic muscle recovery of MRC 4+ and thirteen gained MRC 3 or above. The AIN to MUN nerve transfer provides meaningful intrinsic recovery in the majority of traumatic high ulnar nerve injuries. This procedure should be routinely considered, however, warrants further research to validate the optimum technique.